Production Process of Jamu Nano Teknologi PT AICI Cirebon. West Java, Indonesia - Nurudin , Arif (Greenation Research & Yayasan Global Resarch National, 2023)
PT. Autoimmune Care Indonesia (AICI) is an MSME engaged in the production of herbal medicines with nanotechnology formula particle size. Starting with the results of the lecturers' research inventory that failed to convince BPOM to issue its distribution permit, then a new formula was prepared according to BPOM standards and finally succeeded in obtaining its distribution permit. This study aims to determine the production process of nanotechnology herbs at AICI using observation methods. The results showed that the production process of PT Autoimmune Care Indonesia's nano technology herbal medicine with products in the form of capsules consists of the processing of raw materials and the processing of herbal medicine. The raw material processing process includes raw material handling, compounding, size reduction, sieving, and drying. The herbal medicine processing process includes IPC inspection, final products, quality control, and sanitation. Quality control consists of checking no batch/production code, degree of fineness (< 1000 nanometers), and weight uniformity. Sanitation consists of sanitation of rooms and equipment, sanitation of employees, and waste treatment. Guidance and supervision are carried out by BPOM West Java Province intensively.